Du modèle républicain français à sa marginalisation (1848-1914) - Paolo Benvenuto; Jean-Yves Frétigné (Laboratoire Italien)
Contrary to a widely-held view, the ideals and practices of French republicans never were a model to copy for their Italian counterparts who took part in the intellectually decisive yet short-lived experience of the republics during the revolutionary biennio of 1848-1849. Even in the eyes of its supporters with the strongest conviction (Ferrari), they were debated in order to adapt them to local and historical traditions (Montanelli), when they were not criticized (Mazzini) or simply abandoned in favor of other political horizons (Cattaneo). Following the birth of the Kingdom of Italy, absorbed and like engulfed by the reference to France – a country that both fascinated and irritated Italians – the republican regime of France lost some of its appeal among the Italian republican family even if the latter never hesitated to defend it in times of tension between Rome and Paris and to acknowledge the merits of its values and achievements.